Production of Waterprof Coating from Oil Derived from Coprocessing of High Density Polyethylene, Coal, Lube Oil, and Used Tyre - Duangcha, Apinya; Rattanadechsopa, Padungsak (Engineering and Applied Science Research, 2013)
Asphalt emulsion for waterproof coating consists of asphalt, water, emulsifier, and additives, Experiments were done to investigate the preparation procedure and the composition. After the formula was obtained, asphalt was then replaced by residue (boiling point > 370ºC) from coprocessing of high density polyethylene, coal, lube oil, and used tyre. However, the emulsion of residue gave poor quality. Thereford, asphalt was mixed with the residue and the preparation procedure ts as following. Asphalt 38% by weight of asphalt emulsion (without additives) was melted and mixed with oil from copeocessing of high density polyethylene, coal, lube oil, and used tyre (bp 250 to > 370 ºC) 14%, and pine oil 5%, at 85 ºC . The asphalt solution was blended with emulsifier solution (75 ºC), which consists of a surfactant, nony! Phenol ethoxylate (TERIC N 100), and carboxyvinyl polumer 4-6% and water 38% by weight. The additives slurry was to be added into the asphalt solution. The slurry was formed by blending CaCo3 , tale, BaSO4 30-90 gram into 150 g of water at 60 ºC followed by bentonite clay 4-7 g and 1-3 g of hydroxyethylcellulose, the latter was used to create gelation. The weight ratio of the asphalt emulsion : the additives slurry is 4:1. The asphalt solution was mixed with the additives slurry using a surring rod. The test results of asphalt emulsions using anionic emulsifier (Nansa. HS 80/SPF), eationic emulsifier (CTAB), and nonionic emulsifier (TERIC N100) were compared. The results showed that the asphalt emulsion using TERIC N100, gave the best performance. It was able to dry within 24 h, stable under heat at 100 ºC, and resisted water and ultraviolet ray. Coating on tile, asphalt emulsion produced from oil derived from coprocessing showed no water penetration.